Determinants of utilization of eye care services in a rural adult population of a developing country (2016)
Purpose: To describe the factors that determine the utilization of eye care services in a rural community in South‑Western Nigeria. Methods: A descriptive cross‑sectional survey using a multistage sampling technique was conducted. The main outcome measure was self‑reported previous consultation of an orthodox medical facility for eye care. Results: The study sample included 643 participants. Only 122 (19%) respondents had previously visited orthodox facilities in search of eye care and 24% of those with presenting visual acuity <6/18 had sought eye care. Characteristics associated with previous utilization of eye care services were age of ≥70 years (odds ratio [OR] = 1.7, P = 0.02); male gender (OR = 1.5, P = 0.04); literacy (OR = 1.7, P = 0.007); and residing close to an eye care facility (OR = 2.8, P < 0.001). Blind respondents were three times more likely to seek eye care (P < 0.001). Regression analysis revealed that factors associated with increased likelihood of utilization of eye care services included age ≥70 years; literacy; residence close to an eye facility; being diabetic or hypertensive; history of ocular symptoms, and blindness. Conclusions: These findings suggest that a significant proportion (75%) of adults in the study area are not utilizing eye care services and that blindness is an important determinant of utilization of eye care services. Health education and awareness campaigns about the importance and benefits of seeking eye care early, and the provision of community‑based eye care programs are essential to boost the uptake of eye care services in this community as well as other rural areas of West Africa.